LEADERSHIP LEARNING FOR STUDENTS THROUGH STRENGTHENING ORGANIZATIONAL EMPOWERMENT IN ISLAMIC BOARDING SCHOOLS - Hasan Baharun; Miftahul Huda; Silvy Qotrun Nada (STAI Ma'had Aly Al-Hikam Malang, 2023)
This study analyses the learning process of student leadership in Islamic boarding schools through organizational empowerment. This research was conducted at the Nurul Jadid Islamic Boarding School, Probolinggo, with a qualitative approach through case studies. Data collection techniques used are interviews, observation, and documentation. The data analysis was carried out in a structured and systematic manner, starting from data collection, data reduction, data display, and drawing conclusions. The study results show that the learning process of learning student leadership is carried out through five stages: direction, training, assignment, escort, and approach. This leadership study shows that the organization's cadre system can run well and create good leaders who can carry out the mandate and carry out their duties properly.